Evolution of nutritional status of infants infected with the human immunodeficiency virus - Vânia Aparecida Leandro-Merhi; Maria Marluce dos Santos Vilela; Marcos Nolasco da Silva; Fábio Ancona Lopez; Antônio de Azevedo Barros Filho (São Paulo Medical Journal, 2000)
CONTEXT: There are today only a limited number of studies defining growth parameters and nutritional status for HIV children. OBJECTIVE: To study the nutritional status of infants infected with the human immunodeficiency virus. TYPE OF STUDY: Longitudinal study. SETTING: Department of Pediatrics, Faculty of Medical Sciences, UNICAMP, Campinas, Brazil. PARTICIPANTS: One hundred and twenty-four children born to HIV infected mothers were evaluated from birth until the age of two years. They were subdivided into two groups: 71 infected children and 53 non-infected children. MAIN MEASUREMENTS: Growth was evaluated in both groups by comparing Z-scores for weight/age (w/a), length/age (H/a) and weight/length (w/H) (using the NCHS curves as reference). RESULTS: The Z-score analyses showed that there was a significant difference between the two groups for all the variables studied, except for the H/a value at 3 months of age and the W/H value at 21 months of age, which showed P > 0.05. CONCLUSIONS: The growth of infected infants was observed to be severely affected in comparison with that of seroreversed infants in the same age groups. Although clinical manifestations may take time to appear, the onset of growth changes begin soon after birth.